Evaluating a wellness intervention including micro-practices for healthcare professionals before and during COVID-19 - Reyes-Chacón, Maria Teresa; Ramírez-Martínez, Flor Rocio; Márquez-Miramontes, Blanca; Leiner, Marie (Horizonte Sanitario, 2022)
Objective: To describe, with a mixed design study, healthcare professionals’ pre-post descriptive measures of quality of life (subjective wellness) and prolonged fatigue, as well as an improvement in overall wellness and satisfaction regarding micro-practices as a result of participation in a wellness intervention before and during COVID-19. Material and Methods: This study had a mixed design involving two independent groups of healthcare professionals participating in a wellness intervention with micro-practices before and during COVID-19. The intervention contained multimodal presentations with animated cartoon stories, comics, storytelling, readings, breathing, mindfulness and visualization exercises, adapted from second-order factors in the Indivisible Self model. Pre-post descriptive measures of quality of life (subjective wellness), prolonged fatigue, as well as improvement in overall wellness and satisfaction regarding micro-practices were collected. Results: Attending to either wellness interventions before or during COVID-19 had a positive and, in some cases significant, effect on important indicators of quality-of-life and prolonged fatigue among healthcare professionals. A qualitative analysis indicated a subjective improvement in overall wellness and satisfaction regarding the use of micropractices included in the wellness interventions, regardless of whether these were presented in person or virtually. Most participants subjectively indicated that they improved in the targeted indicators, especially achievement of better wellness. Conclusions: During ordinary and extraordinary circumstances, healthcare professionals require specific interventions that act primarily to provide them with strategies that can improve physical, emotional, and spiritual health. Use of micro-practices in multimodal workshops to improve healthcare practitioner wellness is a successful tool for learning or remembering the importance of pausing during daily clinical activities and refocusing their energy. Keywords: Holistic health; Health care providers; Health promotion, Working Conditions.